PENGAMBILAN KEPUTUSAN DENGAN PENDEKATAN NON-NUMERICAL MULTI EXPERT-MULTI CRITERIA DALAM PENANGANAN KECACATAN PRODUKSI TUBE PADA PT. BONA METAL PACKAGING - Nunung Nurhasanah; Duffi Januwar (JURNAL TEKNIK INDUSTRI, 2012)
PT. Bona Metal Packaging is a company that move within area of making alumunium tube. The company will be hard to compete if the product result often get defect in production time that the rate of production defect in ranging at 10%, so hopefully there is alternative solution that the company need the most this moment. The objective of this research is to analyze priority solution in minimize tube defect in production process with the use of semi automatic machine.This research begin with finding the cause factor of defect in tube production. Then formulate and choose alternative solution with the use of method non-numerical multi expert multi criteria decision making (ME-MCDM). Base on the result so the problem lies on the operator then need to making efficient use of the operator. The usefullness can be done with the training of operator.